2020
DOI: 10.3389/fneur.2020.569446
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Detection Method for Phosphorylated α-Synuclein in Parkinson Disease by Skin Biopsy

Abstract: Background: Recent studies have found deposition of phosphorylated α-synuclein (p-syn) in Parkinson disease (PD) patients' skin, indicating p-syn may be a potential biomarker of PD. However, the sensitivity of the p-syn detection varied largely from 5. 3 to 100%, this influenced the clinical use of this detection method to some extent. Objective: This study aimed to optimize the skin biopsy method for detecting p-syn deposition in patients with PD. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…Skin samples were fixed in 4°C cold Zamboni (G2190, Solarbio) for 24–48 h. The tissues were embedded in paraffin and 4-μm serial sections were sliced. Standard pathological examinations included haematoxylin and eosin (HE) staing, anti-ubiquitin antibody (ab7780, Abcam, UK) immunostaining ( 6 ). The presence of eosinophilic or ubiquitin-positive inclusion bodies in the nuclei of sweat gland cells, fibroblasts, and fat cells was observed at 100 × magnification under light microscope (Ni-U, Nikon, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Skin samples were fixed in 4°C cold Zamboni (G2190, Solarbio) for 24–48 h. The tissues were embedded in paraffin and 4-μm serial sections were sliced. Standard pathological examinations included haematoxylin and eosin (HE) staing, anti-ubiquitin antibody (ab7780, Abcam, UK) immunostaining ( 6 ). The presence of eosinophilic or ubiquitin-positive inclusion bodies in the nuclei of sweat gland cells, fibroblasts, and fat cells was observed at 100 × magnification under light microscope (Ni-U, Nikon, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic value of other biospecimens, such as those from saliva, tears, or the microbiome, is yet to be explored in patients with iRBD, and longitudinal studies are required to establish whether such biosamples will support the understanding of disease onset and progression in LBP [ 198 ]. Finally, novel methods have been developed to investigate αSyn in iRBD cases by using Real-Time Quaking-Induced Conversion assays (RT-QuIC) [ 199 201 ]. These assays can detect αSyn seeding activity in different LB-associated conditions with a high sensitivity and specificity [ 202 ].…”
Section: Prodromal Pd As a Clinical Surrogate For Early Pathological ...mentioning
confidence: 99%
“…For anti-pSyn, higher number of biopsy sites (≥5 versus ≤4) also correlated with higher sensitivity (0.90 versus 0.67, respectively) but not specificity (1.00 versus 1.00), whereas the number of examined sections or the specific anti-pSyn antibody did not significantly alter diagnostic accuracy. However, an analysis of pSyn positivity rate in relation to both skin section thickness and number was not performed; since the pSyn positivity rate increases with higher number [259,261] and thicker sections analyzed [266], this likely influenced the observed pSyn rate. Furthermore, in contrast to the results reported in the aforementioned meta-analysis [265], the recently published multicenter Systemic Synuclein Sampling Study (S4) found a low sensitivity of just 24.1%, with an unchanged 100% specificity, for skin biopsy in the diagnosis of PD [267].…”
Section: Diagnosis Of Parkinson's Diseasementioning
confidence: 99%